2019
DOI: 10.1371/journal.pone.0209163
|View full text |Cite
|
Sign up to set email alerts
|

Low, borderline and normal ankle-brachial index as a predictor of incidents outcomes in the Mediterranean based-population ARTPER cohort after 9 years follow-up

Abstract: BackgroundGuidelines recommended adopting the same cardiovascular risk modification strategies used for coronary disease in case of low Ankle-brachial index (ABI), but here exist few studies on long-term cardiovascular outcomes in patients with borderline ABI and even fewer on the general population.AimThe aim of the present study was to analyze the relationship between long-term cardiovascular events and low, borderline and normal ABI after a 9-year follow up of a Mediterranean population with low cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…Recently, borderline ABI has become accepted as a concept that refers to values between 0.90 and 0.99. Many cohort studies suggest that borderline ABI seems to be associated with increased cardiovascular morbidity and mortality [ 15 , 16 , 17 , 21 ] in comparison to the normal ABI range of 1.00–1.40. An IMPACT-ABI study on symptomatic peripheral arterial disease (PAD) patients demonstrated that even a 10% higher MACE at 4 years and cardiovascular death [ 17 ] among the borderline ABI group compared to ABI range category 1.00–1.40 is in line with the findings of an ARTPER cohort study with a 9-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, borderline ABI has become accepted as a concept that refers to values between 0.90 and 0.99. Many cohort studies suggest that borderline ABI seems to be associated with increased cardiovascular morbidity and mortality [ 15 , 16 , 17 , 21 ] in comparison to the normal ABI range of 1.00–1.40. An IMPACT-ABI study on symptomatic peripheral arterial disease (PAD) patients demonstrated that even a 10% higher MACE at 4 years and cardiovascular death [ 17 ] among the borderline ABI group compared to ABI range category 1.00–1.40 is in line with the findings of an ARTPER cohort study with a 9-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…These included high-risk patients diagnosed with cardiovascular (CVD) disease [ 18 ], burdened with CVD risks factors [ 11 ], symptomatic and asymptomatic PAD [ 9 , 12 , 17 ], and diabetes mellitus [ 13 , 15 , 18 ]. The risk was demonstrated in the primary care setting [ 10 , 13 ], and in population-based studies [ 4 , 5 , 8 , 16 19 ], alike. This was further confirmed in systematic reviews and meta-analyses [ 16 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ankle-brachial index (ABI) 0.9 has been used to diagnose peripheral arterial disease (PAD), even at the pre-clinical stage [1]. Low ABI is associated with atherosclerosis of coronary and carotid arteries [2][3][4][5][6], and increased all-cause and cardiovascular mortality [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. ABI of more than 1.4, an index of arterial stiffness, has also been associated with adverse outcome, especially in older subjects [8,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the ARTPER population-based cohort with low cardiovascular risk has been used to evaluate the incidence of vascular events, improvements made to the reclassification of cardiovascular risk scales following the addition of the ABI, as well as low, borderline, and normal ABI as a predictor of incidents events [ 21 , 22 , 23 ]. This study is focused on prevalent and incident cardiovascular outcomes and their relationship with ABI to evaluate the recurrence of cardiovascular events in a general population over the age of 49.…”
Section: Discussionmentioning
confidence: 99%